2013
DOI: 10.1016/j.jjcc.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, management, and outcomes for patients during hospitalization due to worsening heart failure—A report from the Japanese Cardiac Registry of Heart Failure in Cardiology (JCARE-CARD)

Abstract: The characteristics, clinical status, and laboratory data on admission in patients hospitalized with worsening HF were similar between the present study and previous Japanese and western studies. Management was also similar except for higher use of carperitide and ARB. The most striking difference between Japanese registries and those from the USA and Europe was the longer length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 33 publications
4
56
2
1
Order By: Relevance
“…Coronary artery disease, as the etiology of HF, is relatively lower in Japan than in Western countries 29, 30. Use of angiotensin‐converting enzyme inhibitors and β‐blockers was comparably lower.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Coronary artery disease, as the etiology of HF, is relatively lower in Japan than in Western countries 29, 30. Use of angiotensin‐converting enzyme inhibitors and β‐blockers was comparably lower.…”
Section: Discussionmentioning
confidence: 97%
“…Use of angiotensin‐converting enzyme inhibitors and β‐blockers was comparably lower. Angiotensin receptor blockers were more commonly used in Japan, while angiotensin‐converting enzyme inhibitors were more frequently used than angiotensin receptor blockers in Western countries 30. Although the mean length of hospital stay was considerably longer than in Western countries,29, 30 in‐hospital mortality was comparable, and mortality rate after discharge was lower in Japan than in Western countries 29…”
Section: Discussionmentioning
confidence: 99%
“…We also compared these data with those from Japanese HF registries, including the acute decompensated HF syndromes (ATTEND) registry, 11 the Japanese Cardiac Registry of Heart Failure in Cardiology (JCARE-CARD), 12 and the Heart Institute of Japan-Department of Cardiology (HIJC)-HF Registry. 13 …”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…However, to date, no randomized clinical trials have evaluated the chronic effects of loop diuretics on the long-term outcomes of such patients 38) . Previous subanalyses of randomized clinical trials have demonstrated that the use of diuretics is associated with poor outcomes in patients with CHF [40][41][42] . The present study also showed that the use of furosemide is significantly and independently related to poor outcomes in CHF patients.…”
Section: Effects Of Medication On the Outcomes Of Chf Patientsmentioning
confidence: 99%